Global burden and trends of hypertension-related chronic kidney disease attributable to high body mass index or low physical activity: an analysis based on global burden of disease study 2021 data - Lin, Xiaohua; Miao, Kaiyi; Huang, Kaiqi; Xu, Yanfang; Wang, Yujia (Frontiers in Nutrition, 2026)
BackgroundHypertension-related chronic kidney disease (HT-CKD) represents a global health threat exacerbated by modifiable metabolic risks. Elevated body mass index (BMI) and low physical activity contribute to the development of hypertension and subsequent HT-CKD. This study quantified the global burden of HT-CKD attributable to elevated BMI or low physical activity from 1990 to 2021 and projected future trends to 2050.MethodsBased on the Global Burden of Disease (GBD) 2021 data, deaths, disability-adjusted life years (DALYs), and age-standardized rates (ASRs) of HT-CKD attributable to elevated BMI or physical inactivity were analyzed. Temporal trends of the disease burden from 1990 to 2021 were assessed using a linear regression model. Future burden was forecasted to 2050 using the autoregressive integrated moving average (ARIMA) model and the exponential smoothing (ES) model.ResultsIn 2021, HT-CKD attributable to elevated BMI caused 179,788 deaths and 4.26 million DALYs globally, representing increases of 392.9 and 322.2% since 1990. HT-CKD attributable to low physical activity caused 4,479 deaths and 77,879 DALYs, with similar substantial growth. ASRs for deaths and DALYs showed significant global upward trends from 1990 to 2021 for both risk factors. North Africa had the highest ASRs of death and DALYs for HT-CKD attributable to elevated BMI. For HT-CKD attributable to low physical activity, North Africa and South Africa recorded the highest ASRs of death and DALYs, respectively. The overall disease burden increased with age, peaking in populations aged ≥80 and reaching maximal ASRs in the ≥95-year age group for both metrics and risk factors. Gender disparities revealed higher absolute deaths and DALYs in men for HT-CKD attributable to elevated BMI, but ASR growth was rapid in women for HT-CKD attributable to low physical activity. Across all sociodemographic index (SDI) quintiles, disease burden increased significantly. High-SDI regions showed the steepest ASR growth for HT-CKD attributable to elevated BMI and to low physical activity, whereas low-SDI regions had the slowest growth. Both ARIMA and ES models indicated continued increases in deaths and DALYs attributable to both risk factors from 2022–2050, especially for elevated BMI.ConclusionElevated BMI is the dominant metabolic driver of HT-CKD burden, with physical inactivity playing a significant role. This burden demonstrates pronounced demographic and geographic disparities, highlighting the need for urgent, targeted public health interventions to combat obesity and promote physical activity.